Icelandic Culture From the Perspective of Foreigners - Meyer, Sophie Christin, 1987- (2012)
The development of globalization initiated an increase in international business relations and cross-cultural communication. Both depend on cultural factors, at a national and business level. However, a lot of managers lack the knowledge or ability of how to arrange a base of good communication which diminishes misunderstandings. The Icelandic nation is a very small nation, with approximately 320.000 inhabitants in 2012. Its smallness has been a reason why there were less studies and estimations on the Icelandic culture. A lot of researchers have been developing methods to estimate and analyze culture to increase cultural intelligence. Well known are David C. Thomas and Kerr Inksson for their model of cultural intelligence, Edward T. Hall for studies of communication in management, Fons Trompenaars and Charles Hampden-Turner for their model of seven orientations in culture and Geert Hofstede for his model of cultural dimensions. The few estimations which exist about the Icelandic culture all relate to Hofstede´s model of cultural dimensions. To enable the comparison of the results, this study focuses on the use of a transformed questionnaire (VSM94), which was originally designed by Geert Hofstede. The study was anonymous and respondents were found by convenience, at the University of Iceland, University of Reykjavik and several companies in Iceland. The purpose of this research is to measure the Icelandic culture from the perspective of foreigners who live and work/study in Iceland and are able to compare Icelandic culture to their own culture. Their point of view gives Icelanders an idea about how others see or understand them, and enables the opportunity for a better understanding of cross-cultural communication and work processes in Iceland.